Career prospects of undergraduate female students in the Nigeria Police Force - Buhari, Maryam T. (International journal of police science & management, 2018)
The percentage of women serving in the Nigeria Police Force (NPF) is still small despite efforts to reduce the gender gap. Against this background, this study examined undergraduate female final-year students’ career prospects in the NPF. Expectancy theory was utilised as a theoretical framework. Data were generated through the use of questionnaires and in-depth interviews with 310 female final-year students at two federal universities who were selected through a multistage sampling technique. Although respondents were familiar with police duties, the majority (72%) were unwilling to join the NPF. Also, a connection exists between perceived gender roles and respondents’ future career prospects in the NPF (χ2 = 24.411; P= 0.000066). The NPF should exert more effort towards breaking the masculine-occupation overtone associated with policing.